Experimental evaluation of a passive indirect solar dryer for agricultural products in Central Mozambique. Issue 11 (28th September 2021) - Matavel, Custodio E.; Hoffmann, Harry; Rybak, Constance; Hafner, Johannes M.; Salavessa, João; Eshetu, Shibire Bekele; Sieber, Stefan
Abstract: Post‐harvest losses are one of the major livelihood challenges for farmers in the Global South. The use of drying technologies to preserve agricultural products has been promoted as a particular solution to address this challenge. In this regard, we designed and tested a passive indirect solar dryer for drying agricultural products as an alternative to open sun drying (OSD) in Gurue district, Central Mozambique, using amaranth leaves and maize. In addition, a sensorial analysis was conducted by randomly selecting a group of 60 adults who evaluated the texture, aroma and color of dried amaranth and maize grains. Compared to OSD, the passive indirect solar dryer reduced drying time and increased the thermal efficiency. Evaluation of sensory quality attributes showed that passive indirect solar drying outperforms OSD. Practical applications: This study evaluates the performance of a passive indirect solar dryer, a sustainable alternative to conventional food preservation technologies (e.g., refrigeration) that are not affordable to resource‐constrained communities. The use of passive solar dryers, if carried out correctly, creates the possibility for poor rural households to safely store and increase shelf life of food. In addition, the acceptability of products dried in the passive indirect solar dryer is evaluated. Thus, the study also provides insights on passive solar dryer potential for preserving the quality of the final product.